Identification of two functional regions in Fis: the N-terminus is required to promote Hin-mediated DNA inversion but not lambda excision. - Osuna, R (1991)
The Fis protein of E. coli binds to a recombinational enhancer sequence that is required to stimulate Hin-mediated DNA inversion. Fis is also required for efficient lambda prophase excision in vivo. The properties of mutant Fis proteins were examined in vivo and in vitro with respect to their stimulatory effects on these two different site-specific DNA recombination reactions. Both recombination reactions are dramatically affected by mutations altering a helix-turn-helix DNA binding motif located near the Fis C-terminus (residues 74-93). These mutations invariably decrease DNA binding affinity and some cause reduced DNA bending. Mutations in the Fis N-terminal region reduce or abolish the stimulation of Hin-mediated DNA recombination by Fis, but have little or no effect on DNA binding or lambda excision. We conclude that there are at least two functionally distinct domains in Fis: a C-terminal DNA binding region that is required for promoting both DNA recombination reactions and an N-terminal region that is uniquely required for Hin-mediated inversion.